Correction: Multidimensional assembly using layer-by-layer deposition for synchronized cardiac macro tissues. Issue 36 (4th June 2020) - Jang, Yongjun; Jung, Da Jung; Choi, Seung-Cheol; Lim, Do-Sun; Kim, Jong-Hoon; Jeong, Gi Seok; Kim, Jongseong; Park, Yongdoo
Abstract : Correction for 'Multidimensional assembly using layer-by-layer deposition for synchronized cardiac macro tissues' by Yongjun Jang et al., RSC Adv., 2020, 10, 18806–18815, DOI: ; 10.1039/D0RA01577F .